Multiagent Systems Simulation of Dengue in Minas Gerais (Brazil) - Borges, Katia Cristina A. Damaceno; Reis, Willian Magno Pereira; Oliveira, Alcione de Paiva (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Due to high rates of spread of Dengue fever, as well as high impact on global health and its high cost to public coffers, it is necessary a study on appropriate measures to be taken prior to installation of the epidemic. However, due to the high complexity of the variables involved, it is difficult to describe or make predictions about the advance of the epidemic. Thus, this paper proposes the modeling and simulation of a subsequent multi-agent system applied to the scenario of Dengue in Brazil. The modeling was performed using the software Netlogo and the chosen endemic region was Uberaba in Minas Gerais-Brazil. The results showed that the simulator behaved in a manner consistent with the field data.